A reestruturação do sistema bancário no Brasil após o ano de 2000 através do uso de novas tecnologias: a hegemonia da cidade de São Paulo - Souza, Agnaldo Martins de (2009)
This dissertation covers the changes that occurred in the restructuring of the Brazilian bank system, its hegemony over the territory particularly the bank concentration that exists in the Southeastern Region, especially in the Sao Paulo State, with a deeper analysis of the Sao Paulo Capital City. The dissertation analyzes the technical and technological transformations that occurred in the bank sector and the offer of jobs of the Brazilian banks, pointing out the hegemony that both the Sao Paulo State and the Sao Paulo Capital City exert regarding the other Brazilian capital cities and the other Brazilian Regions - North, Northeast, Mid-West and South. It is also analyzed the evolution of the Brazilian bank system, as from the year 2000 up to 2008, with the purpose of understanding the process of national coverage of the bank branches over the whole Brazilian territory, in addition to the corresponding non-banking services, customer services through the Internet and the mobile phone, the dismissals that occurred in the sector, in addition to the modernization of the banks with the implementation of the new technologies that are focused on the bank sector, as well as the new trends that have to do with the implementation of new technologies and services in the banks. The dissertation covers the restructuring process of the National Financial System, the new approaches for management and the bank restructuring, and the impacts that the aforementioned set of factors caused over the possibility of keeping jobs for bank employees in Brazil. The analysis will make clear the hegemony that the banks exert over some of the capital that circulates in the country as well as the control that the bank sector exerts over the performance of the non-banking activities regarding companies that are leaders in the national market